2023
DOI: 10.3390/pr11061851
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Paddy Harvesting Systems toward Low-Carbon Mechanization in the Future: A Case Study in Sri Lanka

Abstract: In this study, three paddy harvesting systems, manual harvesting of paddy (MHP), reaper harvesting of paddy (RHP), and combine harvesting of paddy (CHP), were evaluated considering field capacities, field efficiencies, time and fuel consumption, mechanization indices, greenhouse gas emissions, straw availability, and direct and indirect costs. Field experiments were conducted in the North Central Province of Sri Lanka. The effective field capacity, field efficiency and fuel consumption of the combine harvester… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Although organic fertilizer application in paddy fields brings many environmental benefits, one study conducted in Japan has shown that complete organic paddy cultivation including, organic fertilizer, and organic pests and weeds management makes comparatively higher environmental impacts (Hokazono and Hayashi, 2012). But, now higher attention is paid to low-carbon mechanization to reduce the emission by a higher degree of machinery use in organic farming (Kahandage et al, 2023).…”
Section: Comparison Of the Characterized Resultsmentioning
confidence: 99%
“…Although organic fertilizer application in paddy fields brings many environmental benefits, one study conducted in Japan has shown that complete organic paddy cultivation including, organic fertilizer, and organic pests and weeds management makes comparatively higher environmental impacts (Hokazono and Hayashi, 2012). But, now higher attention is paid to low-carbon mechanization to reduce the emission by a higher degree of machinery use in organic farming (Kahandage et al, 2023).…”
Section: Comparison Of the Characterized Resultsmentioning
confidence: 99%